Pengaruh Jumlah Penduduk, Pengangguran, dan Kemiskinan terhadap Pertumbuhan Ekonomi di Provinsi Jawa Tengah Tahun 2010-2020 - Faisal Amanullah; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2023)
Economic growth is the process of increasing the production capacity of an economy which is realized in the form of regions. An area is said to experience economic growth if there is an increase in GRDP (Gross Regional Domestic Product) in the area. The economic problem in Central Java Province is the problem of the number of people still living in poverty and becoming unemployed. The high level of poverty and the high rate of unemployment if not addressed immediately will lead to poor people and unemployment which continues to grow every year. This study aims to analyze the effect of population, unemployment, and poverty on economic growth in Central Java Province in 2010-2020. The method used is multiple linear regression to determine the effect of population, unemployment, and poverty on economic growth in Central Java Province. The independent variables used in this study consisted of population, unemployment and poverty, the dependent variable used in this study was economic growth. The results of this study note that the population variable has a partial and significant positive effect on economic growth. Unemployment and poverty variables have a partial and significant negative effect on economic growth.